2021
DOI: 10.1080/09654313.2021.1944065
|View full text |Cite
|
Sign up to set email alerts
|

Coworking spaces and creative communities: making resilient coworking spaces through knowledge sharing and collective learning

Abstract: Sharing of spaces enhances networking and collaboration in cultural and creative industries on both formal and informal levels. Nevertheless, there is a lack of awareness concerning coworking spaces (CWS) and their resilience through knowledge sharing in communities, especially in space-community-coworker interactions. The aim is to identify how CWS enhance their resilience through knowledge sharing in communities and develop collective learning in local creative ecosystems to promote adaptation. A total of 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 50 publications
1
3
0
1
Order By: Relevance
“…First, according to the results, the co-working arrangement of the RDS had a positive impact upon the team productivity. Similar to prior research on space and productivity (e.g., Bednář et al, 2021; Clarke, 2016; Mariotti et al, 2021), feedback from both learning designers and teachers indicated their preference for the arrangement, as it facilitated their interprofessional communication. This positivity may also be attributed to the fact that physical proximity allowed quick distribution of roles responsibilities, and direct communication between team members, and access to rapid peer feedback.…”
Section: Discussionsupporting
confidence: 53%
“…First, according to the results, the co-working arrangement of the RDS had a positive impact upon the team productivity. Similar to prior research on space and productivity (e.g., Bednář et al, 2021; Clarke, 2016; Mariotti et al, 2021), feedback from both learning designers and teachers indicated their preference for the arrangement, as it facilitated their interprofessional communication. This positivity may also be attributed to the fact that physical proximity allowed quick distribution of roles responsibilities, and direct communication between team members, and access to rapid peer feedback.…”
Section: Discussionsupporting
confidence: 53%
“…Much of the existing literature identifies CWS communities as being for broadly instrumental entrepreneurial ends (Bouncken et al, 2020a; Jamal, 2018; Kubatova, 2016), despite disagreements regarding the different kinds of communities they generate and support. Bueno et al (2018) find a positive influence of social interactions in coworking environments on productivity, while other literature identifies the role CWS have in start-up ecosystems and cultures of innovative entrepreneurialism concentrated in urban centres (Bednár et al, 2023; Fraiberg, 2017; Gauger et al, 2021). Research on communities of practice can illuminate this further by theorising CWS as sites where users with shared concerns regularly interact, and in doing so form a particular domain, community and prevailing practice (Brown and Duigid, 1991; Wenger, 2011) which can advance both individual and collective ends.…”
Section: Theorising and Contextualising The Cws Sectormentioning
confidence: 96%
“…(#12) Vagyis a már említett csomóponti szerep, a kreatív gazdaságban zajló klaszteresedés elősegítése lehet a közösségi munkavégzés legfontosabb "konkrét" eredménye. Jelenleg a hálózati együttműködés még nem erős -több interjúnk is széttagoltságról és egyéni túlélésről tanúskodik -, vagyis a kreatív ökoszisztéma még valóban korai szakaszában jár, a tudásmegosztáson és kollektív tanuláson alapuló előnyök (Bednář, Danko, Smékalová 2021) még nem jelentősek, pedig éppen ezek járulnának hozzá a közösségi reziliencia (Aldrich, Meyer 2015) megerősítéséhez.…”
Section: öSszefoglalásunclassified